Al-Qardawi’s Thought on Zakat of Stocks in a Modern Industry: an Experience of Indonesia - Dakhoir, Ahmad (Fakultas Syariah IAIN Purwokerto, 2019)
This paper studies on al-Qaradawi’s stock zakat in the millennial era and modern industry. The main purpose of the study is to elaborate several points of significance of stock zakat within huge benefits of the capital market in Indonesia; therefore, this paper is a content analysis type of study using a literature study approach. In the meantime, the primary resource for the literature is a kitab (book) entitled fiqh al-zakat by Yusuf al-Qaradawi published in 1973. The crucial point emphasized by the paper is that al-Qaradawi’s thoughts and opinions on stock zakat have been proven that he was such a progressive ulama (Islamic scholar), even he is in the current industrial revolution era. He has shown that such critical and innovative thoughts, either in zakat or other aspects. Al-Qaradawi points out that stock is categorized into traded goods so that it is an object of zakat; 2.5% of total stock should be taken out to those deserving. Indonesia as a country with the biggest Muslim majority in the world has been implementing stock zakat when one of the companies namely PT Henan Putihrai Sekuritas issued this kind of zakat. This made Indonesia the first country to proceed with stock zakat as the application of al-Qaradawi’s thoughts and opinions after 45 years.